Factors and co-factors influencing clinical manifestations in nsLTPs allergy: between the good and the bad - Ridolo, Erminia; Barone, Alessandro; Ottoni, Martina; Peveri, Silvia; Montagni, Marcello; Nicoletta, Francesca (Frontiers in Allergy, 2023)
Non-specific lipid transfer proteins (nsLTPs) are a family of plant pan-allergens that represent the primary cause of food allergies in the Mediterranean area, characterized by a wide range of clinical manifestations, ranging from the total absence of symptoms up to anaphylaxis. This wide variety of symptoms is related to the intrinsic capacity of nsLTPs to cause an allergic reaction in a specific subject, but also to the presence of co-factors exacerbating (i.e., exercise, NSAIDs, PPIs, alcohol, cannabis, prolonged fasting, menstruation, acute infections, sleep deprivation, chronic urticaria) or protecting from (ie., co-sensitization to PR10, profilin or polcalcin) severe reactions. In this picture, recognizing some nsLTPs-related peculiarities (i.e., route, type and number of sensitizations, concentration of the allergen, cross-reactions) and eventual co-factors may help the allergist to define the risk profile of the single patient, in order to promote the appropriate management of the allergy, from dietary advices up to the prescription of life-saving epinephrine autoinjector.